Impact of dynamic balance and hip abductor strength on chronic ankle instability - Alejandro López-Valenciano; Francisco Ayala Rodríguez; José Luis López-Elvira; David Barbado Murillo; Francisco José Vera-García (Asociación Española de Ciencias del Deporte, 2016)
Introduction: Ankle sprains are injuries that commonly occur during physical activity. They constitute between 15-75% of all sport injuries, and they can develop into chronic ankle instability (CAI) and functional disability. Subjects with CAI have exhibited diminished dynamic balance and weakness in the hip abductor muscles. Therefore, the purpose of this study was to investigate whether dynamic balance and hip abduction strength measures were related to the level of severity in CAI. Material y Methods: 40 students with Cumberland ankle instability tool (CAIT), defined by the CAIT, were divided into two groups: severe instability and mild instability group. Participants were assessed in dynamic balance and hip abduction strength. Results: No significant correlations were found between CAIT, Y-Balance and abduction strength variables in any group. Y-Balance test explained 24.7% of the CAI variance in the regression analysis, being statistically significant in the predictive model (p < 0.01). Hip abductor strength was rejected from the model. Discussion: This study reinforces the necessity of the inclusion of balance exercises for the lower extremity as a key content when designing rehabilitation programs for athletes with CAI. However, hip abductor strength exercises are still remains controversial. This knowledge would allow sports therapists to design more effective rehabilitation programs.